DEVELOPMENT OF LATENT LIP PRINTS ON MULTICOLOURED SURFACES, A PROBLEM RESOLVED USING FLUORESCENT DYES (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Fingerprints are one of the most effective methods of identification. However lip prints can also provide   important information. At the present time more and more people use protecting lipsticks and permanent  lipsticks. With these lipsticks a latent lip print is generated by contact with a surface and, like with the latent  fingerprints occur, this latent lip print can be developed.  In a previous work the use of lysochromes, specifically Sudan III, Oil Network Or and Sudan Black, was used  for the development of latent lip prints on porous and non porous surfaces, is proposed. These reagents are very  effective even for old latent lip prints . But when prints are left on very dark or multicoloured surfaces, some  problems of contrast may hide the development.  The work that follow study the usefulness of fluorescent reagents to develop latent lip prints on very dark or  multicoloured surfaces. Preliminary analysis have demonstrated the efficiency of Nile Red to develop old prints  on different dark colour surfaces (specifically blue, red and black). Current research tests the usefulness of  fluorescent reagents on both multicoloured and dark coloured surfaces.
Keywords: Lipstick; Latent print; Forensic identification; Nile Red; Luminescence